Human capital, fertility and growth - Oded Galor (Brown University, Department of Economics, 2006)
The demographic transition that swept the world in the past 140 years has been identified as one of the prime forces in the transition from stagnation to growth. The unprecedented increase in population growth during the early stages of industrialization was ultimately reversed. The rise in the demand for human capital in the second phase of industrialization brought about a significant reduction in fertility rates and population growth in various regions of the world, enabling economies to convert a larger share of the fruits of factor accumulation and technological progress into growth of income per capita.
Keywords: O11; O14; O33; O40; J11; J13; 330; Humankapital; Demographischer Übergang; Fruchtbarkeit; Wirtschaftswachstum; Westeuropa